2007
DOI: 10.1063/1.2717692
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reaction modeling for hypervelocity collisions between O and HCl

Abstract: The sensitivity of a rarefied-to-transitional flow to the fidelity of the chemical reaction model is investigated for a new molecular dynamics/quasiclassical trajectory (MD/QCT)-derived model and compared with the widely used total collision energy (TCE) model of Bird. For hypervelocity collisions that occur in the space environment, it is not clear, a priori, that the TCE model will provide reasonable results for the required high energy range and, particularly, if strong favoring of the reaction among differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In Eqs. (7) and (8), 6 dependent on the vibrational states of the molecule. In the previous thermo studies of N 2 , the same result was also observed in that the state-specific tota mostly depend on the vibrational states [19].…”
Section: (4)mentioning
confidence: 99%
See 3 more Smart Citations
“…In Eqs. (7) and (8), 6 dependent on the vibrational states of the molecule. In the previous thermo studies of N 2 , the same result was also observed in that the state-specific tota mostly depend on the vibrational states [19].…”
Section: (4)mentioning
confidence: 99%
“…In this energy e dissociation of H 2 are occurred by coupling with the rovibrational states of H 2 [7, specific total cross sections can accurately describe the nonequilibrium chemical (6) where Ω (2,2) is collision integral and T is equilibrium temperature. The collision integral Ω (2,2) are taken from the works of Stallcop et al [24] and Park et al [25].…”
Section: (4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the O+SO 2 reaction cross section has been modeled by MD/QCT simulations at eight relative velocities and five internal energies of the target SO 2 [1]. Similar MD/QCT collision data for high velocity O+HCl collisions were used in DSMC simulations of a lateral side jet on a rocket [22]. In the current work, the DSMC simulation includes the O+SO 2 →2O+SO reaction cross section versus internal energy at a specific relative velocity through polynomial curve-fits to the MD/QCT dissociation cross section data at 4, 8, 16, 30, 45, 60, and 80 km/s.…”
Section: Modelmentioning
confidence: 99%